Changes in self-esteem in participants associated with Weightloss and Maintenance of Commercial Weight Management Programme - Stubbs, James; Hillier, Sarah; Pallister, Carolyn; Avery, Amanda; McConnon, Aine; Lavin, Jacquie (Symbiosis, 2015)
Introduction and methods: This study examined associations between weight loss, its maintenance and self-esteem in 292 members of a commercial weight management organisation, Slimming World. Self-esteem was measured with the Rosenberg self-esteem questionnaire adapted to 5-point Likert scales. Associations between dimensions of self-esteem and weight change were examined by correlation and regression using the GENSTAT 5 statistical program. Results: Mean (SD) weight on joining the CWMO was 89.0 (20.0) kg; time taken to reach current weight was 16.3 (13.5) months. Mean (SD) weight change was -15.6 (11.4) kg and BMI change was -5.7 (4.0) (both p < 0.001), maintained for 11.7 (12.8) months. Percent variance in weight change associated with each component of self-esteem is given in parentheses. All weight changes were negative. Participants reported a decrease in sense of failure (3.9%) and an increase in self-respect (3.0%) and self-pride (2.4%). Self-satisfaction (12.8%), feelings of self-achievement (10.6%), positive attitudes towards themselves (9.9%), sense of self-worth (10.6%) and self-efficacy (7.3%) all significantly increased in association with reaching and maintaining their current weight (all p < 0.001). Multiple regression analysis showed that age, gender, height and start weight accounted for 35.4% of the variance in weight change. Self-esteem components of the model accounted for 50.4% of the variance in weight change. Conclusion: Successful weight loss and maintenance was associated with significant reported improvements in self-esteem in members of a Commercial Weight Management Organisation.